Modeling Students’ Attitudes toward Procedural Text Comprehension in TikTok-Based Multimodal Writing - Wendy Fernando Bangun; Hadiyanto; Andiopenta Purba; Diah Octavia Kusuma Wardani (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
Multimodal learning activities using short-form video platforms such as TikTok are increasingly used in writing instruction. However, it remains unclear whether these activities meaningfully support students’ procedural writing development. This study examines how TikTok-based procedural writing activities relate to students’ attitudes toward writing and their understanding of procedural-text organization. A quantitative survey was conducted involving 102 students who participated in TikTok-based writing projects, and the data were analyzed using partial least squares structural equation modeling (PLS-SEM). The findings show that information and research literacy skills and supportive learning conditions contribute positively to students’ attitudes toward writing, while perceived barriers such as limited experience and time pressure negatively influence these attitudes. Conventional collaborative writing does not show a significant relationship with writing attitudes. The study also finds that students with more positive attitudes toward writing tend to demonstrate stronger understanding of procedural-text structure and sequencing. These findings indicate that the effectiveness of TikTok-based writing activities depends not only on the use of digital media but also on how the learning environment supports students during the writing process. The study highlights the importance of combining multimodal creativity with sufficient instructional guidance in procedural writing instruction.